1991
DOI: 10.1210/jcem-73-2-421
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Patients with Mild Thyroid Abnormalities: Maternal and Neonatal Repercussions*

Abstract: A prospective study was undertaken during pregnancy in 120 euthyroid women presenting with mild thyroid abnormalities (TA): 11 with a past history of thyroid disorder, 44 with goiter, 20 with nodules, and 45 with thyroid autoantibodies. The aims of the study were to assess whether the pattern of thyroid alterations during gestation was different in women with TA compared to that in healthy control pregnant subjects and to evaluate possible obstetrical and neonatal repercussions. The overall prevalence of under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
4
14

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(180 citation statements)
references
References 12 publications
8
154
4
14
Order By: Relevance
“…The relationship between thyroid dysfunction, thyroid autoimmunity and the risk of preterm delivery (PTD) and complications of pregnancy has been well described [5,6]. The rate of PTD varied from 4 to 26.8 % in TPOAb-positive women and 3-8.2 % in TPOAbnegative controls [22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between thyroid dysfunction, thyroid autoimmunity and the risk of preterm delivery (PTD) and complications of pregnancy has been well described [5,6]. The rate of PTD varied from 4 to 26.8 % in TPOAb-positive women and 3-8.2 % in TPOAbnegative controls [22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…eral studies risk of fetal loss and preterm delivery [5,6]. However, whether the TPOAb positivity is in some pregnant women only a laboratory phenomenon or it is always accompanied by morphological changes in TUS remains unclear.…”
Section: Relationship Of Thyroid Texture To Thyroid Laboratory Tests mentioning
confidence: 99%
“…The studies differed in various aspects. Some had followed a cohort (235)(236)(237)248,250,252,253,(260)(261)(262)(263)(264)(265)(266)(267)(268)(269)(270)(271) (B,A,B,B,B,B,B,A,B-B) and others were "case-controlled" studies (251,254,(272)(273)(274)(275) (C,C,C,C,C).…”
Section: What Is the Role Of Thyroid Autoimmunity In Fertility And Prmentioning
confidence: 99%
“…Earlier studies have reported increased prevalence of congenital anomalies (10-20%), perinatal mortality (20%) and impaired mental and somatic development (50-60%) in new born of untreated hypothyroid mothers. 5,6 The prevalence of preterm babies (gestational age <37 weeks) in group A is found to be 2%. And the prevalence of preterm babies in group B is 6%.…”
Section: Discussionmentioning
confidence: 99%